Teachers’ Perceptions of the Effective EFL Teachers at Junior and Senior High Schools in Padang - Putri Rahima Sari; Sitti Fatimah (Universitas Negeri Padang, 2020)
The importance of being an effective EFL teacher becomes a crucial issue because in Indonesian educational curriculum, English is taught as a subject matter at junior and senior high schools. English teachers, hold significant roles inside of the classroom in order to meet the objectives of curriculum. This study aimed to investigate the teachers’ perception toward the characteristics of effective EFL teachers at junior and senior high school in Padang, from the aspects of pedagogical competency, English language pedagogical competency, personal competency, social competency, and professional competency. The data were collected by using two-section questionnaire which consisted of close and open-ended questions distributed to 26 English teachers of junior and senior high schools in Padang. The results showed that the stakeholders emphasized on pedagogical competency, such as preparing English lesson well (M=4.88) and managing class time well (M=4.81) as the most important characteristics of an effective EFL teacher. As a whole, teachers perception are at good category.